Effects of hemochromatosis and transferrin gene mutations on peripheral iron dyshomeostasis in mild cognitive impairment and Alzheimer's and Parkinson's diseases - Mariani, Stefania; Ventriglia, Mariacarla; Simonelli, Ilaria; Spalletta, Gianfranco; Assogna, Francesca; Bucossi, Serena; Siotto, Mariacristina; Melgari, Jean-Marc; Vernieri, Fabrizio; Squitti, Rosanna (Frontiers in Aging Neuroscience, 2013)
Deregulation of iron metabolism has been observed in patients with neurodegenerative diseases. We have carried out a molecular analysis investigating the interaction between iron specific gene variants [transferrin (TF, P589S), hemochromatosis (HFE) C282Y and H63D)], iron biochemical variables [iron, Tf, ceruloplasmin (Cp), Cp:Tf ratio and % of Tf saturation (% Tf-sat)] Impairment (MCI), 78 Parkinson’s disease (PD) patients and 139 healthy controls to investigate mechanisms of iron regulation or toxicity. No difference in genetic variant distributions between patients and controls was found in our Italian sample, but the stratification for the APOE e4 allele revealed that among the APOE e4 carriers was higher the frequency of those carriers of at least a mutated TF P589S allele. Decreased Tf in both AD and MCI and increased Cp:Tf ratio in AD vs. controls were detected. A multinomial logistic regression model revealed that increased iron and Cp:Tf ratio and being man instead of woman increased the risk of having PD, that increased values of Cp:Tf ratio corresponded to a 4-fold increase of the relative risk of having MCI, while higher Cp levels were protective for PD and MCI. Our study has some limitations: the small size of the sample, one ethnic group considered, the rarity of some alleles which prevent the statistical power of some genetic analysis. Even though they need confirmation in larger cohorts, our data suggest the hypothesis that deregulation of iron metabolism, in addition to other factors, has some effect on the PD disease risk.